Pathogen reduction by ultraviolet C light effectively inactivates human white blood cells in platelet products. Issue 2 (19th August 2014) - Pohler, Petra; Müller, Meike; Winkler, Carla; Schaudien, Dirk; Sewald, Katherina; Müller, Thomas H.; Seltsam, Axel
<x xml:space="preserve">Abstract</x> Background Residual white blood cells (WBCs) in cellular blood components induce a variety of adverse immune events, including nonhemolytic febrile transfusion reactions, alloimmunization to HLA antigens, and transfusion‐associated graft‐versus‐host disease (TA‐GVHD). Pathogen reduction (PR) methods such as the ultraviolet C (UVC) light‐based THERAFLEX UV‐Platelets system were developed to reduce the risk of transfusion‐transmitted infection. As UVC light targets nucleic acids, it interferes with the replication of both pathogens and WBCs. This preclinical study aimed to evaluate the ability of UVC light to inactivate contaminating WBCs in platelet concentrates (PCs). Study Design and Methods The in vitro and in vivo function of WBCs from UVC‐treated PCs was compared to that of WBCs from gamma‐irradiated and untreated PCs by measuring cell viability, proliferation, cytokine secretion, antigen presentation in vitro, and xenogeneic GVHD responses in a humanized mouse model. Results UVC light was at least as effective as gamma irradiation in preventing GVHD in the mouse model. It was more effective in suppressing T‐cell proliferation (>5‐log reduction in the limiting dilution assay), cytokine secretion, and antigen presentation than gamma irradiation. Conclusions The THERAFLEX UV‐Platelets (MacoPharma) PR system can substitute gamma irradiation for TA‐GVHD prophylaxis in platelet (PLT) transfusion. Moreover, UVC treatment achieves suppression of antigen presentation and inhibition of cytokine accumulation during storage of PCs, which has potential benefits for transfusion recipients.